Analisis Tata Kelola Anggaran Pemberdayaan Komunitas Adat Terpencil - Jan H.R. Ubey; Arius Kambu; Halomoan Hutajulu (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2022)
The purpose of this research is to analyze budget governance for the empowerment of remote indigenous communities (KAT) in West Papua. This study uses qualitative data and quantitative data sourced from the Social Service of West Papua Province and the Directorate of Remote Indigenous Community Empowerment of the Ministry of Social Affairs. The data were analyzed using a qualitative descriptive approach. The results of the study indicate that budget management for KAT empowerment in West Papua includes (a) planning and budgeting; (b) budget execution; (c) administration; and (e) reporting and accountability. The KAT empowerment program in West Papua consists of (a) mapping and determining the location of KAT empowerment; (b) empowering KAT human resources; (c) socio-cultural, economic, and environmental empowerment; (d) assistance in structuring the social environment; (e) life insurance assistance; and (f) assistance with work equipment, household equipment, and seed assistance. The problems of KAT empowerment in West Papua include (a) the lack of budget for the implementation of empowerment; (b) minimal cross-sectoral roles; (c) low quality of human resources; and (e) dependence.